“Bumi Becaro” Environmentally Community Empowerment Program to Supporting Post-Pandemic Economic Recovery for the Community of Payakabung Village, Ogan Ilir District - Saddam Husein; Purwanto, Wahyu; Anindita Paramasatya (Prospect Publishing, 2023)
This article explains how the condition of the community in the Payakabung Village area, North Indralaya District, Ogan Ilir Regency after the Covid 19 pandemic has not fully recovered, then there is the role of the surrounding company, namely PT PLN Indonesia Power UPDK Keramasan ULPL Indralaya in helping restore the socio-economic conditions of the community through the